Performances of Bali cow kept by the palm oil farmers in Rokan Hulu, Riau. Issue 1 (November 2021) - Baliarti, E; Setiawan, I; Widi, T S M; Suhartanto, B; Maulana, H; Atmoko, B A; Astrini, A L
Abstract: The development of the beef cattle population in Indonesia can be done by increasing the cows' performance keeping by oil palm farmers. The research aimed to study Bali cows' production system and performance maintained by oil palm farmers in Karya Mulya Village, Rambah Samo District, Rokan Hulu Regency, Riau. Fifteen farmers as respondent with 33 of their Bali cows were the subjects of observation. This research was conducted using the interview method, focused on the production system, body size, and reproductive performance. Data were analyzed descriptively, quantitative, and qualitative. The study results on body size showed that the Bali cows had a chest circumference of 156.68±7.07 cm, shoulder height 112.73±8.86 cm, absolute body length 113.77±5.26 cm, relative body length 105±6.89 cm, body weight 253.65±28.64 kg, and body condition score 2.91±0.50. Reproductive performance includes the calving interval is 376.96±77.65 days, weaning time is 7.74±1.16 months, postpartum estrus 72.00±36.81 days, postpartum mating 72.00±36.81 days, service per conception 1.23±0.8, calf mortality 6.25%, calf weaning weight at 205 days is 97.59±22.88 kg, cows reproductive index 0.96 ± 0.26 and productivity 68.23 ± 46.89. It concluded that Bali cows raised by oil palm farmers in Rokan Hulu, Riau had good performance and body size.